Time Course and Mechanisms Underlying Standing Balance Recovery Early After Stroke: Design of a Prospective Cohort Study With Repeated Measurements - Schröder, Jonas; Saeys, Wim; Yperzeele, Laetitia; Kwakkel, Gert; Truijen, Steven (Frontiers in Neurology, 2022)
Introduction: Although most stroke survivors show some spontaneous neurological recovery from motor impairments of the most-affected leg, the contribution of this leg to standing balance control remains often poor. Consequently, it is unclear how spontaneous processes of neurological recovery contributes to early improvements in standing balance. Objective: We aim to investigate (1) the time course of recovery of quiet stance balance control in the first 12 weeks poststroke and (2) how clinically observed improvements of lower limb motor impairments longitudinally relate to this limb’s relative contribution to balance control. Methods and analysis: In this prospective longitudinal study, a cohort of 60 adults will be recruited within the first 3 weeks after a first-ever hemispheric stroke and mild-to-severe motor impairments. Individual recovery trajectories will be investigated by means of repeated measurements scheduled at 3, 5, 8 and 12 weeks poststroke. The Fugl-Meyer Motor Assessment and Motricity Index of the lower limb serve as clinical measures of motor impairments at the hemiplegic side. As soon as subjects are able to stand independently, bilateral posturography during quietly standing will be measured. First, the obtained center-of-pressure (COP) trajectories at each foot will be used for synchronization and contribution measures that establish (a-)symmetries between lower limbs. Second, the COP of both feet combined will be used to estimate overall stability. Random coefficient analyses will be used to model time-dependent changes in these measures and, subsequently, a hybrid model will be used to investigate longitudinal associations with clinically observed improvements in motor impairments. Discussion: The current study aims to investigate how stroke survivors ‘re-learn’ to maintain standing balance as an integral part of daily life activities. The knowledge gained through this study may contribute to recommending treatment strategies for early stroke rehabilitation targeting behavioral restitution of the most-affected leg or learning to compensate with the less-affected leg. Trial Registration: The study protocols from which participants will be recruited for this investigation are registered online (ClinicalTrials.gov Identifier: NCT03728036; NCT03727919).